Comparative evaluation of clinical efficacy of coronally advanced flap alone and in combination with placental membrane and demineralized freeze-dried bone allograft in the treatment of gingival recession - Priyanka Chopra; Jayashree Kassal; Sujata Surendra Masamatti; Harpreet Singh Grover (Wolters Kluwer Medknow Publications, 2019)
Background: Guided tissue regeneration is a very commonly employed technique for treating recession defects. However, achieving the required space beneath the membrane is often difficult. Aim and Objectives: The purpose of the present study was to compare and evaluate the clinical efficacy of coronally advanced flap (CAF) alone or in combination with amnion membrane (AM) or chorion membrane (CM) and demineralized freeze-dried bone allografts (DFDBAs) in the management of gingival recession (GR) defects. Materials and Methods: The sample size (Miller's Class I and Class II GR-type defects) consisted of thirty patients which were stratified into three groups randomly (ten for each group). Group A patients were treated with only CAF and Group B patients were treated by CAF in combination with CM and DFDBA. Similarly, Group C patients were treated by CAF in combination with AM and DFDBA. Clinical parameters such as gingival index, GR depth, GR width, relative attachment level, and width of keratinized tissue were assessed at baseline and 3 months postoperatively. Results: Inter- and intragroup data were analyzed by paired t-test. The percentage of root coverage obtained in the study groups was 60%, 78%, and 63%, respectively, for Groups A, B, and C. Statistically significant difference was obtained in the clinical parameters of Group B which was treated with CM and DFDBA. Conclusions: Combination of DFDBA and placental membrane (chorion/amnion) in CAF procedure provided an additional benefit over CAF alone in the treatment of Class I and II GR defects.